PENGARUH KINERJA KARYAWAN TERHADAP KEPUASAN TAMU MENGINAP DI GRAND ROCKY HOTEL BUKITTINGGI - Putra, Syahrial (journal of residu, 2019)
This study aims to determine the effect of employee performance on guest satisfaction staying at the Grand Rocky Hotel Bukittinggi. This type of research is classified as associative quantitative research with a simple linear regression test. The population in this study were all guests who stayed at the Grand Rocky Hotel in the last 1 months. The research sample amounted to 30 guests who were staying with the sampling technique was sampling quota. The technique of data collection is done using a questionnaire (questionnaire) with a Likert scale that has been tested for validity and reliability. Data were analyzed by simple linear regression testing through the help of the SPSS Computer Program version 16.00. The results showed: 1) The performance of Grand Rocky Hotel employees was very good at 86.33%, 2) Guest satisfaction was in the very satisfied category (56.67%), 3) The results of simple linear regression test with a significance level of 0.041, there were no positive influences and significant between employee performance and guest satisfaction with a r value of 0,778 (sig 0,003) with an insignificant interpretation of the effect.